2017
DOI: 10.1016/j.jvs.2016.08.104
|View full text |Cite
|
Sign up to set email alerts
|

Relative value unit-based compensation incentivization in an academic vascular practice improves productivity with no early adverse impact on quality

Abstract: Revenue-improving measures can improve sustainability of a vascular program without negatively affecting patient care as evidenced by the lack of difference in evidence-based core outcome measures in our study period. Further studies are needed to elucidate the long-term effects of incentivization programs on both patient care and program viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This trend is compounded by steadily decreasing federal funding for surgeon scientists and shifts to productivity-based compensation models which result in increased pressure to produce work relative value units. 24 Furthermore, to expedite training and address a workforce shortage, new surgical training models including integrated vascular surgery, integrated thoracic surgery, integrated plastic surgery, and general surgery with early specialization options commonly eliminate dedicated and protected time for research. Expedited surgical training adds the temptation of increased income potential in the form of faster time to practice from medical school which is understandably pursued by medical students in the current climate of soaring costs for medical education.…”
Section: Perspectivementioning
confidence: 99%
“…This trend is compounded by steadily decreasing federal funding for surgeon scientists and shifts to productivity-based compensation models which result in increased pressure to produce work relative value units. 24 Furthermore, to expedite training and address a workforce shortage, new surgical training models including integrated vascular surgery, integrated thoracic surgery, integrated plastic surgery, and general surgery with early specialization options commonly eliminate dedicated and protected time for research. Expedited surgical training adds the temptation of increased income potential in the form of faster time to practice from medical school which is understandably pursued by medical students in the current climate of soaring costs for medical education.…”
Section: Perspectivementioning
confidence: 99%
“…12 Previous studies have shown that their use correlates with patients seen (i.e., throughput), overall revenue, improved clinical outcomes, and concomitant decreases in health care delivery costs. [13][14][15][16] Critics of their use argue that this system correlates poorly with surgical effort/complexity, incentivizes a competitive culture among surgeons, eliminates predictability, and incentivizes the overuse of procedures. 17 Furthermore, relevant to hospital-or academic-based plastic surgeons, some aesthetic procedures do not have associated relative value units, making the quantification of productivity difficult for these procedures.…”
Section: Productivity-based Compensation Models: Relative Value Unitsmentioning
confidence: 99%
“…2,3 There was a significant increase in number of cases for otolaryngology procedures. 3 Generalizations from these studies are limited due to short follow-up times 2 and restriction of analysis to only outpatient procedures. 3 There is a dearth of similar investigations in plastic surgery.…”
mentioning
confidence: 99%